The influence of county-level gender inequality on gender differences in bariatric surgery - Pernat, Claire A. (Tufts Archival Research Center, 2020)
In the United States, around 80% of bariatric surgery patients are female, while obesity rates between genders are similar. This study aims to understand (1) if there is an association between county-level gender inequality and bariatric surgery patient sex and (2) if there is an association between county-level gender inequality and percent female bariatric surgeries.A retrospective analysis of New York’s Statewide Planning and Research Cooperative System between 2010 and 2015 was performed. Our study included New York State adult patients with obesity who underwent bariatric surgery. County-level gender inequality, defined by the United Nation’s Gender Inequality Index, was created with data from Area Health Resources Files, New York State, American Community Survey, and CDC. The dependent variable for the multivariate logistic regression was the sex of the patient, and the dependent variable for the multivariate linear regression was percent female bariatric surgical procedures by county. We adjusted for gender inequality and relevant covariates for both analyses.From 2010 to 2015, 71,364 bariatric surgical procedures were performed in New York’s 62 counties. Females made up 79.15% of the patient population. Bariatric surgery patients residing in counties with high levels of gender inequality were significantly more likely to be female than male (p<0.01). Increased levels of county-level gender inequality were associated with a predicted increase in the percentages of county-level female bariatric surgeries (p<0.05).The gender difference in bariatric surgery patients is influenced by county-level gender inequality. This demonstrates that gender inequality can affect treatment choices and that clinical decisions may be made because of non-clinical reasons. To promote equality in healthcare, isolating clinical and societal influences in the bariatric decision-making process may be beneficial in decreasing gender differences in surgery. Advisor: Dr. Andrea Acevedo.